Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the equation of the tangent line to [tex]\( y = x^2 \)[/tex] at the point [tex]\((1, 1)\)[/tex], we need to follow these steps:
### Step 1: Differentiate the function
The given function is [tex]\( y = x^2 \)[/tex]. We need the derivative of [tex]\( y \)[/tex] with respect to [tex]\( x \)[/tex] to find the slope of the tangent line.
[tex]\[ \frac{dy}{dx} = \frac{d}{dx}(x^2) = 2x \][/tex]
### Step 2: Evaluate the slope at the given point
Now, we evaluate the derivative at the point [tex]\( x = 1 \)[/tex].
[tex]\[ \frac{dy}{dx} \Bigg|_{x=1} = 2 \cdot 1 = 2 \][/tex]
So, the slope of the tangent line at [tex]\( x = 1 \)[/tex] is [tex]\( 2 \)[/tex].
### Step 3: Use the point-slope form of the tangent line
The point-slope form of a line is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( (x_1, y_1) \)[/tex] is the point of tangency and [tex]\( m \)[/tex] is the slope. Here, [tex]\( (x_1, y_1) = (1, 1) \)[/tex] and [tex]\( m = 2 \)[/tex].
[tex]\[ y - 1 = 2(x - 1) \][/tex]
### Step 4: Simplify the equation
Solve for [tex]\( y \)[/tex] to put the equation in slope-intercept form [tex]\( y = mx + b \)[/tex].
[tex]\[ y - 1 = 2x - 2 \][/tex]
[tex]\[ y = 2x - 2 + 1 \][/tex]
[tex]\[ y = 2x - 1 \][/tex]
So, the equation of the tangent line is [tex]\( y = 2x - 1 \)[/tex].
### Step 5: Verify the options
Let's verify which option matches our derived equation:
- [tex]\( y = 2x - 2 \)[/tex]
- [tex]\( y = 2x - 1 \)[/tex] ✔️
- [tex]\( y = 3x + 1 \)[/tex]
- [tex]\( y = 2x + 2 \)[/tex]
### Conclusion
The correct equation of the tangent line to [tex]\( y = x^2 \)[/tex] at [tex]\((1, 1)\)[/tex] is [tex]\( y = 2x - 1 \)[/tex]. Therefore, the correct answer is:
[tex]\[ \boxed{y = 2x - 1} \][/tex]
### Step 1: Differentiate the function
The given function is [tex]\( y = x^2 \)[/tex]. We need the derivative of [tex]\( y \)[/tex] with respect to [tex]\( x \)[/tex] to find the slope of the tangent line.
[tex]\[ \frac{dy}{dx} = \frac{d}{dx}(x^2) = 2x \][/tex]
### Step 2: Evaluate the slope at the given point
Now, we evaluate the derivative at the point [tex]\( x = 1 \)[/tex].
[tex]\[ \frac{dy}{dx} \Bigg|_{x=1} = 2 \cdot 1 = 2 \][/tex]
So, the slope of the tangent line at [tex]\( x = 1 \)[/tex] is [tex]\( 2 \)[/tex].
### Step 3: Use the point-slope form of the tangent line
The point-slope form of a line is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( (x_1, y_1) \)[/tex] is the point of tangency and [tex]\( m \)[/tex] is the slope. Here, [tex]\( (x_1, y_1) = (1, 1) \)[/tex] and [tex]\( m = 2 \)[/tex].
[tex]\[ y - 1 = 2(x - 1) \][/tex]
### Step 4: Simplify the equation
Solve for [tex]\( y \)[/tex] to put the equation in slope-intercept form [tex]\( y = mx + b \)[/tex].
[tex]\[ y - 1 = 2x - 2 \][/tex]
[tex]\[ y = 2x - 2 + 1 \][/tex]
[tex]\[ y = 2x - 1 \][/tex]
So, the equation of the tangent line is [tex]\( y = 2x - 1 \)[/tex].
### Step 5: Verify the options
Let's verify which option matches our derived equation:
- [tex]\( y = 2x - 2 \)[/tex]
- [tex]\( y = 2x - 1 \)[/tex] ✔️
- [tex]\( y = 3x + 1 \)[/tex]
- [tex]\( y = 2x + 2 \)[/tex]
### Conclusion
The correct equation of the tangent line to [tex]\( y = x^2 \)[/tex] at [tex]\((1, 1)\)[/tex] is [tex]\( y = 2x - 1 \)[/tex]. Therefore, the correct answer is:
[tex]\[ \boxed{y = 2x - 1} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.